2020
DOI: 10.1016/j.jpeds.2020.06.041
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Chinese Children Infected with Coronavirus Disease-2019 and with Severe Acute Respiratory Syndrome 2003

Abstract: Objectives To compare the clinical and laboratory features of severe acute respiratory syndrome 2003 (SARS) and coronavirus disease 2019 (COVID-19) in 2 Chinese pediatric cohorts, given that the causative pathogens and are biologically similar. Study design This is a cross-sectional study reviewing pediatric patients with SARS (n = 43) and COVID-19 (n = 244) who were admitted to the Princess Margaret Hospital in Hong Kong and Wuhan Children's Hospital in Wuhan, respectively. Demographics, hospital length of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
0
23
0
1
Order By: Relevance
“…To calculate the prevalence of headache in COVID-19, full-text assessment resulted in the exclusion of 123 articles for the following reasons: case control studies (n=2), case report studies (n=69), case series (n=29), duplicated dataset (n=1), and conducted in specific population only (n=23). The targeted population studies were conducted among healthcare workers 28 31 , diabetic patients 32 , pediatrics 33 , pregnant women 34 , cancer patients 35 , children and young adults 36 40 , patient undergone surgery 41 , critical patients 42 , women undergone delivery 43 , patients with mild-moderate COVID-19 44 46 , patients with gastrointestinal symptoms 47 , patients with severe headache only 48 , and patients with anosmia only 49 . In total, 78 studies were included to calculate the prevalence of headache in COVID-19 and all studies were published in 2020.…”
Section: Resultsmentioning
confidence: 99%
“…To calculate the prevalence of headache in COVID-19, full-text assessment resulted in the exclusion of 123 articles for the following reasons: case control studies (n=2), case report studies (n=69), case series (n=29), duplicated dataset (n=1), and conducted in specific population only (n=23). The targeted population studies were conducted among healthcare workers 28 31 , diabetic patients 32 , pediatrics 33 , pregnant women 34 , cancer patients 35 , children and young adults 36 40 , patient undergone surgery 41 , critical patients 42 , women undergone delivery 43 , patients with mild-moderate COVID-19 44 46 , patients with gastrointestinal symptoms 47 , patients with severe headache only 48 , and patients with anosmia only 49 . In total, 78 studies were included to calculate the prevalence of headache in COVID-19 and all studies were published in 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Alcuni studi retrospettivi hanno riportato alcune differenze nelle manifestazioni cliniche del Covid-19 rispetto a specifiche infezioni respiratorie osservate in età pediatrica. Un'analisi dei sintomi di pazienti con sindrome respiratoria acuta grave 2003 (SARS) e Covid-19 ha riscontrato che i pazienti con SARS presentano più frequentemente febbre, brividi, mialgia, malessere, rinite, mal di gola, tosse produttiva, nausea, cefalea e vertigini 13 . In rapporto ai pazienti con Influenza A, i pazienti con Covid-19 presentano più frequentemente febbre, diarrea o vomito, cefalea, dolore muscolare e toracico, mentre non sono state riportate differenze significative nel confronto con la sintomatologia dei pazienti affetti da Influenza B 14 .…”
Section: Discussioneunclassified
“…Simple measures that appeared to be useful during the SARS epidemic such as temperature screening [ 25 ] may not be sufficient for the COVID-19 pandemic. Compared to the high number of asymptomatic COVID-19 cases, the majority of SARS cases presented with fever, but serological study showed asymptomatic SARS carriers were extremely rare [ 26 , 27 ]. Nevertheless, other measures such the universal use of face masks, border controls, and mandatory self-quarantine policies for travellers returning from high-risk areas should be kept in place until an effective COVID-19 vaccine becomes available [ 28 ].…”
Section: Discussionmentioning
confidence: 99%